Allopurinol in the complex therapy of acute decompensation of heart failure - Laura H. Sarieva; Marina D. Muksinova; Svetlana N. Nasonova; Igor V. Zhirov; Sergey N. Tereshchenko (Consilium Medicum)
Background. Acute decompensation of heart failure (ADHF) is a period of chronic HF, which is characterized by a rapid aggravation/onset of HF symptoms, requiring urgent hospitalization for intensive care and worsening the patient’s prognosis.